Transonic flutter analysis of an AGARD 445.6 wing in the frequency domain using the Euler method. Issue 1 (1st January 2016) - Zhang, Bocheng; Ding, Weilong; Ji, Shengcheng; Zhang, Jiazhen
ABSTRACT: A method based on the Euler equations is proposed for solving transonic flutter problems. The transonic nonlinear flow field with local shock wave/boundary layer interaction is obtained by the Euler/boundary layer equations, and the aerodynamic forces are converted from the time domain to the frequency domain using system identification techniques. The structural dynamic equations in generalized coordinates are adopted for solving structure problems. The method is validated by a flutter boundary prediction of the AGARD 445.6 wing model. The simulation results show that the method presented in this paper is accurate for the prediction of transonic flutter boundary through comparison with experimental data and other simulation results. Furthermore, the present frequency domain method is also much more efficient than the time domain method.